Modern Islamic Eco-Religion: Historical Contexts - Shefer-Mossensohn, Miri (Journal for the study of religion, nature and culture, 2025)
Since Lynn White Jr., an extensive and rich body of literature has emerged, focusing on the intersection of environmental ethics and sustainability education, particularly examining the potential contribution of ecotheology in fostering ecological restoration. This article ventures into the Islamic case, surveying key positions from the 1960s through the early twenty-first century, in English, Arabic, and Turkish. It elucidates the historical contexts that shaped this discursive reality, underscoring intellectual, religious, and sociopolitical trends. The study probes the manifestations of Islamic echotheology within a focal region of the Islamic world—the Middle East—while explicating its connections to global trends. The article further suggests that these circumstances may account for the discrepancy between the robust discursive reality and the relative modest impact of Muslim values and faith-based Muslim actors on local, regional, and global sustainable actions. The deliberate use of ‘ecotheology’ aims to facilitate a dialogical engagement with other world religions.